DOn't lose confidence.
The solution is as follows:
Let x1 and x2 be the respective roots.
So, x1 + x2 = x1*x2....This is a given
When we have a ax^2 + bx + c = 0
=>Sum of the roots is equal to -b/a
=>The product of the roots is qual to c/a
so, in 27x^2 + (3k+9)x - 43 + k = 0
a = 27
b = 3k+9
c = -43 + k
(1)Then, -d/a must = -3k + 9/27
(2)and, c/a must = -43 + k/27
Set these two equations equal to each other and solve for 'k'
That will be your answer.
Pls include reasoning along with all answer posts.
Este examen me conduce jodiendo loco